A new snapping shrimp (Caridea, Alpheidae) from the Pacific coast of Colombia - Christoffersen, Martin L. (1987)
Alpheus wickstenae sp. n. is described and distinguished from the six morphologically most similar species by a combination of characters. It is provisionally situated within the Edwardsii Group of Alpheus.